Characteristics of falls producing hip fracture in patients on oral anticoagulants. Issue 3 (3rd May 2016) - Formiga, Francesc; Chivite, David; Navarro, Margarita; Montero, Abelardo; Duaso, Enric; Ruiz, Domingo; Perez-Castejon, Juan Manuel; Lopez-Soto, Alfons; Corbella, Xavier
Abstract : Objective: To analyze the demographic and clinical characteristics of patients on chronic anticoagulant therapy (CAT) admitted because of a hip fracture secondary to a fall, and to compare with patients not receiving CAT.Methods: A prospective, observational study realized in six hospitals in the Barcelona area. Demographic and clinical characteristics of patients were collected. The index fall characteristics – cause, height, location, and time of occurrence – were evaluated.Results: Of the 1225 patients included, 99 (8%) patients were on CAT. When we compare with the rest logistic regression analysis showed that patients receiving CAT were more likely to be male (odds ratio 3.7), not institutionalized (odds ratio 3.5), to take more number of drugs (odds ratio 1.3), to have dementia (odds ratio 2.1) and stroke (odds ratio 1.7). Results revealed a higher prevalence of combined factors as the cause of the index fall in the group of patients on anticoagulants.Conclusions: Characteristics of falls were very similar when comparing the group of patients receiving CAT with those who did not. A prior history of falls should lead physicians to take actions for preventing falls causing hip fracture, in all patients and particularly in these on CAT.